Pengembangan Media Perkembangbiakan Hewan Pada Mata Pelajaran IPA Kelas 6 SD Untuk Meningkatkan Motivasi Dan Penguasaan Konsep - Bahtiar, Emas; Kusumastuti, Mimin Nurjhani; Sardjijo, Sardjijo (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
This research is a development research that aims to find out the development media that can increase students' motivation and mastery of concepts. The research method used is the development method with the ADDIE design. The instruments used in this study were observation, questionnaires and tests. The results of data analysis for motivation increased from 51.58% before use to 84.36%. The average result of students' mastery of the concept pretest 69.50 and after use 81.5. The conclusion from the research is that media development can increase students' motivation and mastery of concepts.